Epilepsy in MT‐ATP6 ‐ related mils/NARP: correlation of elettroclinical features with heteroplasmy. Issue 3 (21st January 2021) - Licchetta, Laura; Ferri, Lorenzo; La Morgia, Chiara; Zenesini, Corrado; Caporali, Leonardo; Lucia Valentino, Maria; Minardi, Raffaella; Fulitano, Daniela; Di Vito, Lidia; Mostacci, Barbara; Alvisi, Lara; Avoni, Patrizia; et al.
Abstract: The study aims to characterize the epilepsy phenotype of m aternally i nherited L eigh's s yndrome (MILS) and n europathy, a taxia, r etinitis p igmentosa (NARP) due to mutations in the mitochondrial ATP6 gene and to correlate electroclinical features with mutant heteroplasmy load (HL). We investigated 17 individuals with different phenotype, from asymptomatic carriers to MILS: 11 carried the m.8993T> G mutation, 5 the m.8993T> C and one the novel, de novo m.8858G> A mutation. Seizures occurred in 37.5% of patients, EEG abnormalities in 73%. We ranked clinical and EEG abnormalities severity and performed quantitative EEG to estimate Abnormality Ratio (AR) and Spectral Relative Power (SRP). Spearman's rho and Kruskal–Wallis test were used for correlation with heteroplasmy load (HL). HL correlated with disease severity (Rho = 0.63, P  = 0.012) and was significantly higher in patients with seizures or EEG abnormalities ( P  = 0.014). HL correlated with EEG severity score only for the m.8993T> G (Rho = 0.73, P  = 0.040), showing a trend toward a positive correlation with AR and delta SPR, irrespective of the mutation.